Peran Teknologi Fintech Dalam Menumbuhkembangkan Iklim Investasi Reksa Dana Syariah Di Indonesia - Yusuf; Fathmah Hanum (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2020)
The existence of Islamic financial institutions in marketing products using financial technology affects public interest in obtaining alternative investment options. The economic impact of the Covid 19 virus pandemic provides an opportunity for sharia mutual fund products to develop as a source of receiving funds from the public. This study aims to determine the role of Islamic financial technology institutions in improving the investment climate in Indonesian Islamic finance. This qualitative descriptive study was written based on literacy studies from various books and research journals related to Islamic economics and investment. From the results of the research, it can be concluded that Islamic financial institutions that use financial technology have a role in improving the investment climate in Indonesian Islamic finance in the form of convenience and alternative investment options that result in increased returns. Supervision of the activities of sharia financial technology institutions by the Financial Services Authority and BAPEPAM is required in supervising the operations of sharia financial institutions to ensure the level of security of public funds invested in sharia mutual fund investment products.